A transient rise in tropical sea surface temperature during the Paleocene-Eocene Thermal Maximum - J. C. Zachos; M. W. Wara; S. Bohaty; M. L. Delaney; A. Brill; T. J. Bralower; M.R. Petrizzo; I. Premoli-Silva (Science, 2003)
The Paleocene-Eocene Thermal Maximum (PETM) has been attributed to a rapid rise in greenhouse gas levels. If so, warming should have occurred at all latitudes, although amplified toward the poles. Existing records reveal an increase in high-latitude sea surface temperatures (SSTs) (8° to 10°C) and in bottom water temperatures (4° to 5°C). To date, however, the character of the tropical SST response during this event remains unconstrained. Here we address this deficiency by using paired oxygen isotope and minor element (magnesium/calcium) ratios of planktonic foraminifera from a tropical Pacific core to estimate changes in SST. Using mixed-layer foraminifera, we found that the combined proxies imply a 4° to 5°C rise in Pacific SST during the PETM. These results would necessitate a rise in atmospheric pCO 2 to levels three to four times as high as those estimated for the late Pateocene.